Multiomics Landscape Uncovers the Molecular Mechanism of the Malignant Evolution of Lung Adenocarcinoma Cells to Chronic Low Dose Cadmium Exposure - Dai, Shun-Dong; Wang, Shuang; Qin, Ya-Nan; Zhu, Jin-Chao (Frontiers in Oncology, 2021)
Cadmium (Cd) from cigarette smoke and polluted air can lead to lung adenocarcinoma after long-term inhalation. However, most studies are based on short-term exposure to this toxic metal at high concentrations. Here, we investigate the effects of long-term exposure of A549 cells (lung adenocarcinoma) to cadmium at low concentrations using morphological and multiomics analyses. First, we treated A549 cells continuously with CdCl2 at 1μM for 8 months and found that CdCl2 promoted cellular migration and invasion. After that, we applied transmission electron and fluorescence microscopies and did not observe significant morphological changes in Golgi apparatus, endoplasmic reticulum, lysosomes, or mitochondria on Cd treated cells; microfilaments, in contrast, accumulated in lamellipodium and adhesion plaques, which suggested that Cd enhanced cellular activity. Second, by using whole-exome sequencing (WES) we detected 4222 unique SNPs in Cd-treated cells, which included 382 unique non-synonymous mutation sites. The corresponding mutated genes, after GO and KEGG enrichments, were involved mainly in cell adhesion, movement, and metabolic pathways. Third, by RNA-seq analysis, we showed that 1250 genes (784 up and 466 down), 1623 mRNAs (1023 up and 591 down), and 679 lncRNAs (375 up and 304 down) were expressed differently. Furthermore, GO enrichment of these RNA-seq results suggested that most differentially expressed genes were related to cell adhesion and organization of the extracellular matrix in biological process terms; KEGG enrichment revealed that the differentially expressed genes took part in 26 pathways, among which the metabolic pathway was the most significant. These findings could be important for unveiling mechanisms of Cd-related cancers and for developing cancer therapies in the future.